PTU-069 Incidence of and survival following perforated diverticular disease: a population-based cohort study from england. (8th June 2018) - West, Joe; Crooks, Colin; Otete, Harmony; Humes, David
Abstract : Background: Previous studies suggesting the incidence of perforated diverticular disease is increasing are no longer contemporary and were unable to describe trends by age, sex and calendar year. We aimed to provide population based estimates of the incidence of perforated diverticular disease and assess variation by age, calendar time, treatment and sex. Methods: We undertook a historical cohort study using linked primary and secondary care data from 2000–2013 from England. We identified cases of perforated diverticular disease older than 18 years, calculated incidence rates, and modelled variation using Poisson regression along with estimating one year survival with life tables. Results: We identified 2347 cases with an overall incidence of 6.98 per 1 00 000 person years (pyrs) (interquartile range (IQR) 6.70–7.27 per 1 00 000 pyrs). There was an interaction between calendar time, age and treatment (Likelihood Ratio Test p<0.0001). Stratum specific estimates of the increase in incidence for each age group from 2000 to 2013 showed the greatest increase, 49%, in those aged under 45 years who were treated conservatively without surgery (Incidence Rate Ratio 1.49, 95% CI 1.36–1.61) adjusting for sex and region. This increase was seen in conjunction with an increased use of diagnostic imaging especially in the younger age groups. One year survival was highest in those under the age of 65 years who were treated conservatively (96.4%). In those over 65 years one year survival was lower and varied as to whether patients were treated operatively or not (71.4% vs. 50.7%). Conclusions: The incidence of perforated diverticular disease has increased from 2000 to 2013 with the greatest increase in younger age groups who also had the best survival. The increase in incidence in younger groups in part may be due to the identification of patients with localised perforations more frequently identified due to an increase in the use of CT scans.